2019
DOI: 10.13005/bpj/1725
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Treatment Transposed Antidepressant-Like Action in Rats Provoked to Chronic Mild Stress

Abstract: The present study aimed at evaluating the effects of lycopene on CMS-induced depressive-like behavioral changes in Wistar rats. In present study, rodents were selected randomly and grouped in to seven groups. Each group consists of six animals. All the groups are subjected to chronic mild stress in an unpredictable manner except the control group, which is free from stress. Behavioral changes induced during chronic mild stress were assessed by conducting the behavioral tests like forced swim test, sucrose pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Similarly, both histological and ultrastructural examination revealed that the SMG regained its almost normal architecture along with marked enhancement in cellular shape and component of the acini and ducts. The beneficial role of nanolycopene emulsion in improving CUMS-altered SMGs matched that of Kumar et al who evaluated the effects of lycopene on CUMS-induced depressive-like behavioral changes in rats and stated that lycopene possessed antidepressant activity which may be due to its antioxidant effect [32]. Noteworthy, Paruchuri et al reported that lycopene supplementation in rats exposed to CUMS significantly reversed the oxidative stress by increasing the antioxidant enzymes activity including; superoxide dismutase, catalase and glutathione peroxidase enzymes thereby raising the efficiency of antioxidant defense system [31] .…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, both histological and ultrastructural examination revealed that the SMG regained its almost normal architecture along with marked enhancement in cellular shape and component of the acini and ducts. The beneficial role of nanolycopene emulsion in improving CUMS-altered SMGs matched that of Kumar et al who evaluated the effects of lycopene on CUMS-induced depressive-like behavioral changes in rats and stated that lycopene possessed antidepressant activity which may be due to its antioxidant effect [32]. Noteworthy, Paruchuri et al reported that lycopene supplementation in rats exposed to CUMS significantly reversed the oxidative stress by increasing the antioxidant enzymes activity including; superoxide dismutase, catalase and glutathione peroxidase enzymes thereby raising the efficiency of antioxidant defense system [31] .…”
Section: Discussionsupporting
confidence: 57%
“…Depression has a multifactorial etiology comprising functional deficits in monoamine, such as serotonin, and disturbances in the brain’s hypothalamic–pituitary–adrenal (HPA) axis [ 14 ]. In addition, emotional disorders such as anxiety and depression are often associated with a reduction in the activity of antioxidant enzymes in the HPA axis.…”
Section: Introductionmentioning
confidence: 99%